Papilledema in a child with Acute Lymphoblastic Leukaemia during remission-A Case Report - C Vivek Nandini Reddy; M H Patil (Wolters Kluwer Medknow Publications, 2020)
Background: Ocular manifestations of pediatric ALL may be the presenting sign of the disease or may signify leukemic recurrence. Objective: To report papilledema in a diagnosed case of Acute Lymphoblastic Leukaemia during remission. Methods: A case report from a tertiary center in North Karnataka of a 7-year-old male, who is a known case of ALL-L1 and being treated on ICICLE protocol; presents with sudden onset headache and vomiting 7 months after documented remission. Routine blood examination, CSF analysis and MRI brain were performed. Ocular Examination: The anterior segment was normal with visual acuity of 6/6 in both eyes. IDO examination & fundus photography revealed papilledema. Results: The child was diagnosed with secondary viral meningitis based on CSF analysis and the MRI brain showed mild hydrocephalus. Papilledema and general condition of the patient improved on starting steroids and antiviral drugs along with Chemotherapy. Conclusion: Papilledema is a common ocular finding in ALL with CNS involvement, which responded to an established line of management.